PENINGKATAN HASIL BELAJAR PESERTA DIDIK KELAS 5 SDN 02 KARTOHARJO PADA PELAJARAN PENDIDIKAN PANCASILA DENGAN MATERI KERAGAMAN BUDAYA MELALUI PENDEKATAN CULTURALLY RESPONSIVE TEACHING (CRT) - Rizki, Lutfi Etika; Pinkan Amita Tri Prasasti; Istini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to improve the learning outcomes of 5th-grade students at SDN 02 This investigation aims to enhance the educational achievement of fifth-grade pupils at SDN 02 Kartoharjo in Pancasila Education, emphasizing cultural diversity content through the Culturally Responsive Teaching (CRT) approach. The research methodology employed is Classroom Action Research (CAR) comprising two phases. The study participants consisted of 28 fifth-grade students from SDN 02 Kartoharjo. The findings revealed a substantial improvement in student learning outcomes. In the preliminary phase, the average student score was 65.7 with 42.9% classical mastery. In phase I, the average score rose to 74.3 with 67.9% classical mastery. Phase II demonstrated further progress with an average score of 83.2 and 89.3% classical mastery. This study concludes that the CRT approach effectively improves student learning outcomes regarding cultural diversity material in Pancasila Education.